119k views
4 votes
(6-2.7h)+(-1.3j-4)

?

User Bogdacutu
by
5.0k points

2 Answers

2 votes

Answer:

−2.7h−1.3j+2

Explanation:

User Jozef Dochan
by
4.2k points
1 vote

Answer:

= 2 - 2.7h - 1.3j

Explanation:

(6-2.7h)+(-1.3j-4)

we solve the question with the BODMAS

BRACKET

OF

DIVISION

MULTIPLICATION

ADDITION and

SUBTRACTION

(6-2.7h)+(-1.3j-4)

Solve the bracket first

= 6 - 2.7h - 1.3j - 4

Now we collect like terms

= 6 - 4 - 2.7h - 1.3j

= 2 - 2.7h - 1.3j

User Party Ark
by
4.1k points